Dampak penggunaan smartphone pada remaja - Sumiatin, Titik; Ningsih, Wahyu Tri; Yunariyah, Binti; Nugraheni, Wahyuningsih Triana; Agnes, Yeni Lufiana Novita (Holistik Jurnal Kesehatan, 2025)
Background: Smartphone use among adolescents has become a problem widely perceived by parents. The increasing duration of smartphone use over the years has also become a serious issue, prompting complaints from various parties. The various impacts that are beginning to be felt due to smartphone use have prompted some parties to take preventative measures. Purpose: To determine the impact of smartphone use on adolescents. Method: The research design used a descriptive approach, with a population of all adolescents at State Senior High School 2 Tuban. The sample size was 224 respondents, and the sampling technique used was simple random sampling. The research instruments used were a knowledge questionnaire and the Adolescent Sedentary Activity Questionnaire (ASAQ) translated into Indonesian. Results: Of the 224 teenagers who used smartphones, more than half were addicted (61.6%). Impacts found on teenagers due to smartphone use included 78.6% experiencing poor mental health, 31.7% experiencing poor social relationships, the majority (92.9%) experiencing emotional instability, 30.8% engaging in risky behavior, and more than half (60.0%) having inactive physical activity. Conclusion: Smartphone use among adolescents negatively impacts mental health, social relationships, emotional well-being, risky behavior, and physical activity.   Keywords: Adolescents; Impact; Smartphone.   Pendahuluan: Penggunaan smartphone pada remaja saat ini telah menjadi masalah yang banyak dirasakan oleh orang tua.  Peningkatan durasi penggunaan smarthphone dari tahun ke tahun juga menjadi masalah serius yang dikeluhkan berbagai pihak. Banyaknya dampak yang mulai dirasakan akibat penggunaan smartphone, menyebabkan beberapa pihak telah mengambil tindakan pencegahan. Tujuan: Untuk mengetahui dampak penggunaan smartphone pada remaja. Metode: Desain penelitian menggunakan diskriptif dengan populasi seluruh remaja di SMAN 2 Tuban, besar sampel yang digunakan sebanyak 224 responden, teknik pengambilan sampel  simple random sampling. Instrumen penelitian mengadopsi dari kuesioner pengetahuan dan Adolescent Sedentary Activity Questionnaire (ASAQ) yang telah dialihbahasakan ke dalam Bahasa Indonesia. Hasil: Sebanyak 224 remaja yang menggunakan smartphone, lebih dari separuh termasuk dalam kecanduan (61.6%). Dampak yang ditemukan pada remaja akibat penggunaan smartphone, antara lain 78.6% memiliki kesehatan mental yang buruk, 31.7% memiliki hubungan sosial buruk, mayoritas (92.9%) memiliki emosional yang tidak stabil, 30.8% mempunyai perilaku berisiko, dan lebih dari separuh (60.0%) memiliki aktivitas fisik dalam kategori tidak aktif. Simpulan: penggunaan smartphone pada remaja memberikan dampak negatif terhadap kesehatan mental, hubungan sosial, emosional, perilaku berisiko, dan aktivitas fisik.   Kata Kunci: Dampak; Remaja; Smartphone.